Secondary battery, electric device

CN118712454BActive Publication Date: 2026-10-23SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410681206.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2026-10-23
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

[0003]然而,卷芯在铝壳中工作也存在着限制

Benefits of technology

[0030]本申请提供的二次电池中,通过在铝壳基体相对设置的第一面和第二面的至少一者的绝缘层上设置析锂优化层,同时在析锂优化层中引入微胶囊化阻燃剂,并且合理选择析锂优化层的厚度、析锂优化层的密度和微胶囊化阻燃剂的直径,使三者满足特定的关系,一方面能够显著的降低循环过程中拐角受力差异性,增强卷芯循环中拐角区域的受力均匀性,改善卷芯在常温以及低温下循环过程中的析锂现象,另一方面随着循环的进行,卷芯在膨胀的过程中通过挤压析锂优化层能够使得拐角区域的电解液的损耗得以补充;从以上两个方面能够有效的提升二次电池的常温和低温循环性能,同时还能够提升二次电池的安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118712454B_ABST
    Figure CN118712454B_ABST
Patent Text Reader

Abstract

The application provides a secondary battery and a power utilization device, and relates to the technical field of batteries.In the secondary battery provided by the application, a lithium precipitation optimization layer is arranged on the insulating layer of at least one of the first face and the second face of the aluminum shell base body arranged oppositely, microencapsulated flame retardants are introduced into the lithium precipitation optimization layer, the thickness of the lithium precipitation optimization layer, the density of the lithium precipitation optimization layer and the diameter of the microencapsulated flame retardants are reasonably selected, the three satisfy a specific relationship, the lithium precipitation phenomenon and the swelling phenomenon of the corner region in the cycle process of the secondary battery can be effectively improved, the normal temperature and low temperature cycle performance of the secondary battery is improved, and the safety of the secondary battery is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Technology

[0002] Lithium-ion batteries have experienced rapid growth in the global new energy market due to their high energy density, long cycle life, and good safety performance. Among them, square aluminum-cased lithium-ion batteries have become a mainstream choice due to their simple structure, high packaging reliability, high capacity, and flexible customization. In the manufacturing process of lithium-ion batteries, winding is favored by consumers due to its strong integration capabilities and high efficiency.

[0003] However, operating the core within an aluminum casing also presents limitations. First, direct contact between the core and the aluminum casing can cause a short circuit, preventing the battery from functioning properly. Current solutions involve covering the core with an insulating film, which reduces casing efficiency to some extent. Second, during core cycling, stress accumulation at the corners affects the lithium intercalation path, making lithium plating more likely and reducing battery cycle life and safety. Furthermore, the electrolyte is gradually consumed during cycling, potentially leading to insufficient electrolyte supply later on, which exacerbates lithium plating at the corners and further reduces battery cycle life. Summary of the Invention

[0004] The purpose of this application is to overcome the shortcomings of the prior art and provide a secondary battery and power device with excellent cycle performance and high safety.

[0005] To achieve the above objectives, a first aspect of this application provides a secondary battery, including a winding core and an aluminum shell. The winding core has a flat portion and a curved portion. The aluminum shell includes an aluminum shell substrate and an insulating layer disposed on the inner surface of the aluminum shell substrate. The aluminum shell substrate has a first surface and a second surface disposed opposite to each other. A lithium plating optimization layer is disposed on the insulating layer of at least one of the first surface and the second surface. The lithium plating optimization layer includes a microencapsulated flame retardant.

[0006] The lithium plating optimization layer satisfies: 0.0006≤K≤0.07;

[0007] Where K = a × b / d,

[0008] a mm represents the thickness of the lithium plating optimization layer;

[0009] bg / cm 3 Optimize the density of the lithium plating layer;

[0010] dμm is the diameter of the microencapsulated flame retardant.

[0011] As an implementation scheme of this application, at least one of the following conditions must be met:

[0012] a. The thickness 'a' mm of the lithium plating optimization layer is 0.5-2.2 mm;

[0013] b. The density of the lithium plating optimization layer is b g / cm³ 3 It is 0.05-0.5 g / cm³. 3 ;

[0014] c. The diameter dμm of the microencapsulated flame retardant is 10-200μm.

[0015] As an embodiment of this application, the mass percentage of the microencapsulated flame retardant is 2-8% based on the total mass of the lithium plating optimization layer.

[0016] As an embodiment of this application, the lithium plating optimization layer comprises the following components by mass percentage: 83-97% polymer matrix, 2-8% microencapsulated flame retardant, and 1-8% additives.

[0017] As an implementation scheme of this application, at least one of the following conditions must be met:

[0018] d. The polymer matrix includes at least one of polyethylene, polypropylene, polyolefin, polyurethane, polystyrene, and polyvinyl chloride;

[0019] e. The additives include at least one of mica powder, talc powder, glass powder, and calcium carbonate.

[0020] As an embodiment of this application, the microencapsulated flame retardant includes a capsule wall and a capsule core, wherein the mass ratio of the capsule wall to the capsule core is 1:(3-5).

[0021] As an implementation scheme of this application, at least one of the following conditions must be met:

[0022] f. The capsule wall comprises at least one of polyethylene, polypropylene, polystyrene, and polyamide;

[0023] g. The core comprises at least one of alkyl phosphate flame retardants, aryl phosphate flame retardants, organic halogenated flame retardants, and inorganic flame retardants.

[0024] As an embodiment of this application, the lithium plating optimization layer has an arc-shaped portion.

[0025] As an embodiment of this application, the lithium plating optimization layer is disposed opposite to the core bending portion.

[0026] As an embodiment of this application, the difference between the arc radius of the lithium plating optimization layer and the radius of the bending portion of the core is 0.1-2.5 mm.

[0027] As an embodiment of this application, the thickness of the insulating layer is 0.1-0.15 mm.

[0028] In a second aspect, this application provides an electrical device comprising the secondary battery described in this application.

[0029] Compared with the prior art, the beneficial effects of this application are:

[0030] In the secondary battery provided in this application, a lithium plating optimization layer is provided on the insulating layer of at least one of the first and second surfaces of the aluminum shell substrate, which are arranged opposite each other. At the same time, a microencapsulated flame retardant is introduced into the lithium plating optimization layer. The thickness, density, and diameter of the lithium plating optimization layer and the microencapsulated flame retardant are reasonably selected so that the three satisfy a specific relationship. On the one hand, it can significantly reduce the stress difference at the corners during cycling, enhance the stress uniformity in the corner area during core cycling, and improve the lithium plating phenomenon of the core during cycling at room temperature and low temperature. On the other hand, as the cycle proceeds, the core expands and squeezes the lithium plating optimization layer, which can replenish the electrolyte loss in the corner area. From the above two aspects, the cycling performance of the secondary battery at room temperature and low temperature can be effectively improved, and the safety of the secondary battery can also be improved. Attached Figure Description

[0031] Figure 1 Schematic diagram of the untreated aluminum shell structure;

[0032] Figure 2 This is a top view of the aluminum shell after processing in Example 1;

[0033] Figure 3 This is a top view of the secondary battery prepared in Example 1;

[0034] Figure 4 This is a top view of the secondary battery prepared in Example 29;

[0035] Figure 5 This is a top view of the secondary battery prepared in Example 30. Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0037] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0038] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0039] Unless otherwise specified, all reagents or instruments used in this application are commercially available products.

[0040] In one embodiment of this application, a secondary battery is provided, comprising a core and an aluminum shell. The core has a flat portion and a curved portion. The aluminum shell comprises an aluminum shell substrate and an insulating layer disposed on the inner surface of the aluminum shell substrate. The aluminum shell substrate has a first surface and a second surface disposed opposite to each other. A lithium plating optimization layer is disposed on the insulating layer of at least one of the first surface and the second surface. The lithium plating optimization layer comprises a microencapsulated flame retardant.

[0041] The lithium plating optimization layer satisfies: 0.0006≤K≤0.07;

[0042] Where K = a × b / d,

[0043] a mm represents the thickness of the lithium plating optimization layer;

[0044] bg / cm 3 Optimize the density of the lithium plating layer;

[0045] dμm is the diameter of the microencapsulated flame retardant.

[0046] This application research found that the secondary battery provided in this application has a lithium plating optimization layer disposed on the insulating layer of at least one of the first and second surfaces of the aluminum shell substrate, which are arranged opposite each other. At the same time, a microencapsulated flame retardant is introduced into the lithium plating optimization layer. The introduction of the microencapsulated flame retardant, together with the design of the lithium plating optimization layer, can effectively improve the safety of the secondary battery. Furthermore, this application research found that the thickness and density of the lithium plating optimization layer and the diameter of the introduced microencapsulated flame retardant have a certain impact on the cycle performance of the secondary battery, lithium plating in the core corner area, and expansion phenomenon. By limiting the thickness and density of the lithium plating optimization layer and the diameter of the introduced microencapsulated flame retardant to satisfy the relationship 0.0006≤a×b / d≤0.07, this application can significantly reduce the lithium plating and expansion phenomenon in the core corner area during room temperature and low temperature cycling. At the same time, as the cycling progresses, the expansion generated by the core can also prompt the lithium plating optimization layer to replenish the electrolyte consumption in the core corner area, thereby further improving the room temperature and low temperature cycling performance of the secondary battery.

[0047] For example, the lithium plating optimization layer satisfies 0.0006 ≤ a × b / d ≤ 0.07, where K can be any point value or any two points within the range of 0.0006 ≤ a × b / d ≤ 0.07. For example, K can be 0.0006, 0.001, 0.002, 0.003, 0.004, 0.006, 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, etc. 0.02, 0.022, 0.024, 0.026, 0.028, 0.03, 0.032, 0.034, 0.036, 0.038, 0.04, 0.042, 0.044, 0.046, 0.048, 0.05, 0.052, 0.054, 0.056, 0.058, 0.06, 0.062, 0.064, 0.066, 0.068, 0.07.

[0048] This study found that when the lithium plating optimization layer satisfies 0.0006≤K≤0.07, it can effectively balance the uniformity of stress and electrolyte storage capacity in the core corner area, thereby achieving a better improvement in the cycle capacity of the secondary battery and the lithium plating and expansion phenomena in the core corner area.

[0049] In one embodiment, the lithium plating optimization layer satisfies: 0.003 ≤ K ≤ 0.02. For example, K can be 0.003, 0.005, 0.007, 0.009, 0.011, 0.013, 0.015, 0.017, 0.019, or any two values ​​within this range. This application's research found that when the lithium plating optimization layer is further selected to satisfy 0.003 ≤ K ≤ 0.02, the resulting secondary battery exhibits higher cycle retention and less lithium plating in the corner region under both room temperature and low temperature conditions.

[0050] In one embodiment, the thickness 'a' mm of the lithium plating optimization layer is 0.5-2.2 mm.

[0051] For example, the thickness 'a' mm of the lithium plating optimization layer can be any point value or any two point values ​​within the range of 0.5-2.2 mm. For example, 'a' can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, or 2.2.

[0052] In one embodiment, the thickness of the lithium plating optimization layer is adjusted by controlling the mold size used in the preparation process of the lithium plating optimization layer.

[0053] This study found that when the thickness of the lithium plating optimization layer is within a certain range, a good balance can be achieved in terms of occupying space within the aluminum shell of the core and providing buffering and electrolyte caching capabilities. This facilitates the placement of the core during secondary battery fabrication without deformation, while also allowing for expansion space, better controlling the stress uniformity in corner areas, and improving the lithium-ion transport path during cycling, thereby enhancing the overall performance of the secondary battery. Furthermore, the thickness of the lithium plating optimization layer also affects the low-temperature cycling performance of the secondary battery to some extent. Because the lithium plating optimization layer has a porous foamed structure, it possesses a certain thermal insulation effect, thus improving the cycling capability of the secondary battery at low temperatures.

[0054] In one embodiment, the thickness 'a' mm of the lithium plating optimization layer is 1.5-2.0 mm. For example, 'a' can be 1.52, 1.54, 1.56, 1.58, 1.62, 1.64, 1.66, 1.68, 1.72, 1.74, 1.76, 1.78, 1.82, 1.84, 1.86, 1.88, 1.92, 1.94, 1.96, 1.98, or any two values ​​within this range. This application research has found that when the thickness of the lithium plating optimization layer is further selected to be 1.5-2.0 mm, the overall performance of the resulting secondary battery is superior.

[0055] In one embodiment, the density of the lithium plating optimization layer is bg / cm³. 3 It is 0.05-0.5 g / cm³. 3 .

[0056] For example, the density of the lithium plating optimization layer is bg / cm³. 3 It can be 0.05-0.5 g / cm³. 3 The value of any point within the range or the range of any two points. For example, b can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, or 0.5.

[0057] In one embodiment, the density of the lithium plating optimization layer is changed by controlling the amount of raw materials used in the preparation process of the lithium plating optimization layer.

[0058] This study found that the density of the lithium plating optimization layer not only affects its electrolyte storage capacity but also its buffering capacity against expansion at the corner of the winding core, thus impacting the cycle performance of the secondary battery. Further optimization of the lithium plating optimization layer density (bg / cm³) further improved its effectiveness. 3 It is 0.05-0.5 g / cm³. 3 When the secondary battery is obtained, the cycling performance at both room temperature and low temperature is better, and the lithium plating phenomenon in the corner region is not obvious during the cycling process.

[0059] In one embodiment, the density of the lithium plating optimization layer is bg / cm³. 3 It is 0.25-0.4 g / cm³. 3 For example, b can be 0.255, 0.265, 0.275, 0.285, 0.295, 0.305, 0.315, 0.325, 0.335, 0.345, 0.355, 0.365, 0.375, 0.385, 0.395, or any two values ​​within this range. This application's research found that when the density of the lithium plating optimization layer, b g / cm³, is further selected... 3 It is 0.25-0.4 g / cm³. 3 When the time is right, the overall performance of the secondary battery obtained is better.

[0060] In one embodiment, the diameter dμm of the microencapsulated flame retardant is 10-200μm.

[0061] For example, the diameter dμm of the microencapsulated flame retardant can be any point value or any two points within the range of 10-200μm. For example, d can be 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, or 200.

[0062] This study found that the selection of the diameter of the microencapsulated flame retardant affects the stress uniformity of the lithium plating optimization layer and the electrolyte storage capacity therein. When the diameter of the microencapsulated flame retardant is further selected within the range of 10-200 μm, not only can the flame retardant effect be effectively achieved, but also, during cycling, when the corner area expands and squeezes the lithium plating optimization layer, the stress on the lithium plating optimization layer is uniform, and a sufficient amount of electrolyte can be released stably, thereby improving the cycle performance of the secondary battery. Furthermore, the introduction of microencapsulated flame retardants with diameters within this range can also ensure that the density of the lithium plating optimization layer is within the range selected in this application.

[0063] In one embodiment, the diameter dμm of the microencapsulated flame retardant is 50-100μm. For example, d can be 52, 54, 56, 58, 62, 64, 66, 68, 72, 74, 76, 78, 82, 84, 86, 88, 92, 94, 96, 98, or any two values ​​within this range. This application has found that when the diameter dμm of the microencapsulated flame retardant is further selected to be 50-100μm, the overall performance of the secondary battery is better.

[0064] In one embodiment, the diameter of the microencapsulated flame retardant is changed by controlling the preparation process of the microencapsulated flame retardant.

[0065] In one embodiment, the mass percentage of the microencapsulated flame retardant is 2-8% based on the total mass of the lithium plating optimization layer.

[0066] For example, the mass percentage of the microencapsulated flame retardant, based on the total mass of the lithium plating optimization layer, can be any point value or any two points within the range of 2-8%, such as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, or 8%.

[0067] This application research found that the introduction of flame retardants can protect and delay the risk of battery fire when thermal runaway occurs in secondary batteries. However, most flame retardants, due to their inherent physical, chemical, or electrochemical instability, can negatively impact battery performance and cannot be directly added to the battery. This application, by adding flame retardants in a microencapsulated form, avoids these problems and improves the safety of secondary batteries. Specifically, when thermal runaway occurs in a secondary battery, the microencapsulated flame retardant can release its contents to protect and delay the risk of battery fire. Furthermore, by selecting a mass percentage of 2-8% for the microencapsulated flame retardant, good safety performance can be achieved with minimal impact on the performance of the lithium plating optimization layer. Specifically, when the decomposition temperature is reached, the flame retardant can be rapidly released and spread, achieving good coverage and thus achieving the purpose of flame retardancy.

[0068] In one embodiment, the mass percentage of the microencapsulated flame retardant is 4-6% based on the total mass of the lithium plating optimization layer. For example, it can be 4.2%, 4.4%, 4.6%, 4.8%, 5.2%, 5.4%, 5.6%, 5.8%, etc. This application research found that when the mass percentage of the microencapsulated flame retardant is further selected to be 4-6%, the overall performance of the resulting secondary battery is superior.

[0069] In one embodiment, the lithium plating optimization layer comprises the following components by mass percentage: 83-97% polymer matrix, 2-8% microencapsulated flame retardant, and 1-8% additives.

[0070] It should be noted that the polymer matrix in the lithium plating optimization layer can be qualitatively analyzed by infrared (FTIR) and ultraviolet (UV) methods, and quantitatively analyzed by differential scanning calorimetry (DSC); the additives can be qualitatively analyzed by XRD and infrared (FTIR) methods, and quantitatively analyzed by thermogravimetric analysis.

[0071] In one embodiment, the lithium plating optimization layer is prepared by comprising the following raw materials in weight percentages: 75-95% polymer matrix, 2-8% microencapsulated flame retardant, 1-10% additives, and 1-15% foaming agent.

[0072] In one embodiment, the polymer matrix includes at least one of polyethylene (PE), polypropylene (PP), polyolefin (POE), polyurethane (PU), polystyrene (PS), and polyvinyl chloride (PVC).

[0073] In one embodiment, the additive includes at least one of mica powder, talc powder, glass powder, and calcium carbonate.

[0074] In one embodiment, the foaming agent includes at least one selected from carbon dioxide, carbonate, carbon black, azo compounds, sulfonyl hydrazine compounds, propane, and butane.

[0075] This application research found that when the components of the lithium plating optimization layer are further selected to be the specific types mentioned above, it is possible to effectively prepare a lithium plating optimization layer with a density and thickness within the range given in this application, and it has good compatibility with the added microencapsulated flame retardant, which can further improve the overall stress uniformity and safety of the lithium plating optimization layer, thereby improving the comprehensive performance of the secondary battery.

[0076] Meanwhile, depending on the selected polymer matrix and foaming agent, the lithium plating optimization layer provided in this application can be divided into two types based on the cell structure: open-cell structure and closed-cell structure. Among them, open-cell foamed material is a foamed material with continuous physical and gas phases. The matrix material exists as continuous cell walls. The unique three-dimensional open-cell structure has excellent absorption and penetration functions. During the foaming process, the foaming agent in the open-cell foam plastic escapes after the optimization layer is formed. In closed-cell foamed material, most cells are surrounded by complete pore walls and the cells are not interconnected. Closed-cell material has higher mechanical strength and better thermal insulation and buffering properties. Both types of open-cell structures can help achieve the effects of this application.

[0077] In one embodiment, the method for preparing the lithium plating optimization layer includes the following steps:

[0078] S1. Mix the polymer matrix, additives and microencapsulated flame retardant evenly to obtain the mixture;

[0079] S2. After heating the mixture to the foaming temperature, add the foaming agent to foam. After foaming, cool to obtain the lithium-plating optimized layer.

[0080] In one embodiment, the microencapsulated flame retardant comprises a capsule wall and a capsule core, wherein the mass ratio of the capsule wall to the capsule core is 1:(3-5).

[0081] For example, the mass ratio of the capsule wall to the capsule core can be any point value or any two points within the range of 1:(3-5), such as 1:3.0, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4.0, 1:4.2, 1:4.4, 1:4.6, 1:4.8, or 1:5.0.

[0082] This study found that the ratio of the capsule wall to the core of the microencapsulated flame retardant not only affects the safety performance of the secondary battery but also its cycle performance. When the mass ratio of the capsule wall to the core is further selected as 1:(3-5), it can avoid the risk of flame retardant leakage caused by excessively thin capsule walls, which would not only reduce the flame retardant effect but also cause the leaked flame retardant to dissolve in the electrolyte, leading to a deterioration in the cycle performance of the secondary battery. On the other hand, it can avoid the decrease in the amount of flame retardant added due to excessively thick capsule walls, which would affect the flame retardant effect.

[0083] In one embodiment, the capsule wall comprises at least one of polyethylene (PE), polypropylene (PP), polystyrene (PS), and polyamide (PA).

[0084] This application research found that when the capsule wall is made of synthetic polymer, such as the material selected above, the synthetic polymer material has good film-forming properties and strong chemical stability. It can not only form an inert protective film on the flame retardant surface, but also has good compatibility with the lithium plating optimization layer, thereby improving the overall stress uniformity of the lithium plating optimization layer and achieving good comprehensive performance of the secondary battery.

[0085] In one embodiment, the core comprises at least one of alkyl phosphate flame retardants, aryl phosphate flame retardants, organic halogenated flame retardants, and inorganic flame retardants.

[0086] This study found that when the core material includes the above-mentioned types of flame retardants, it can be rapidly released and has a wide coverage area during thermal runaway of the secondary battery, effectively blocking heat transfer, achieving excellent flame retardant effect, and improving the safety performance of the secondary battery.

[0087] For example, the alkyl phosphate flame retardant includes at least one of tributyl phosphate, tris(2-ethylhexyl) phosphate, tris(2-chloroethyl) phosphate, and tris(2,3-dichloropropyl) phosphate; the aryl phosphate flame retardant includes at least one of toluene-diphenyl phosphate, tricresyl phosphate, and triphenyl phosphate; and the inorganic flame retardant includes at least one of tellurium compound, aluminum hydroxide, magnesium hydroxide, borate, and red phosphorus.

[0088] In one embodiment, the method for preparing the microencapsulated flame retardant includes the following steps:

[0089] The capsule wall material is added to a solvent, stirred and heated until the capsule wall material is completely dissolved, then the flame retardant is added and stirred until evenly mixed; the constructed capsule digital model is built using 3D printing technology to obtain the microencapsulated flame retardant.

[0090] In one embodiment, the lithium plating optimization layer has an arc-shaped portion.

[0091] This study found that when the lithium plating optimization layer has an arc-shaped portion, it can provide better buffering capacity and electrolyte buffering capacity; thereby achieving a better improvement in the cycle performance of secondary batteries and a better mitigation of lithium plating and expansion phenomena in the corner area of ​​the core.

[0092] In one embodiment, the lithium plating optimization layer is disposed opposite to the core bending portion.

[0093] This application research found that the aluminum shell substrate has a first surface and a second surface arranged opposite to each other, wherein the first surface and the second surface are arranged opposite to the core bending portion. Furthermore, a lithium plating optimization layer is disposed on the insulating layer of at least one of the first surface and the second surface. Therefore, the lithium plating optimization layer is also arranged opposite to the core bending portion. When this application selects the lithium plating optimization layer to be arranged opposite to the core bending portion, during the operation of the secondary battery, the lithium plating optimization layer arranged opposite to the core bending portion can alleviate the cumulative stress changes in the core bending portion, thereby alleviating the lithium plating and expansion phenomena caused by the cumulative stress changes, and thus improving the cycle life and safety of the secondary battery.

[0094] In one embodiment, the difference between the arc radius of the lithium plating optimization layer and the radius of the core bending portion is 0.1-2.5 mm.

[0095] For example, the difference between the arc radius of the lithium plating optimization layer and the radius of the core bending portion can be any point value or any two points within the range of 0.1-2.5 mm, such as 0.1 mm, 0.3 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.4 mm, or 2.5 mm. This application research found that when the difference between the arc radius of the lithium plating optimization layer and the radius of the core bending portion is further selected to be 0.1-2.5 mm, specifically, when the arc radius of the lithium plating optimization layer is 0.1-2.5 mm larger than the radius of the core bending portion, it not only facilitates the insertion of the core but also provides space for the expansion of the core during the cycling process. This allows for the replenishment of electrolyte by squeezing the lithium plating optimization layer during cycling, optimizing the lithium ion transport path during cycling and improving the cycle performance of the secondary battery.

[0096] In one embodiment, the number of arcuate grooves in the lithium plating optimization layer matches the number of bends in the core.

[0097] In one embodiment, the thickness of the insulating layer is 0.1-0.15 mm.

[0098] For example, the thickness of the insulating layer can be any point value or any two points within the range of 0.1-0.15 mm, such as 0.1 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, or 0.15 mm.

[0099] This application study found that the introduction of an insulating layer can reduce the work of insulating film wrapping the core and improve the efficiency of casing. In particular, when the thickness of the insulating layer is further selected to be 0.1-0.15mm, the processing technology is simpler and it is easier to form an insulating layer with uniform thickness, avoiding the formation of non-insulating areas caused by excessively thin thickness, which would affect the safety of the secondary battery. At the same time, it can also provide sufficient space for the core and avoid the reduction of the energy density of the secondary battery.

[0100] In one embodiment, the insulating layer comprises ceramic particles and an adhesive.

[0101] In one embodiment, the mass ratio of ceramic particles to adhesive in the insulating layer is (85-90):(10-15). For example, it can be 85:15, 86:14, 87:13, 88:12, 89:11, 90:10, etc.

[0102] In one embodiment, the ceramic particles include at least one of SiC, AlN, Al2O3, and MgSiO3; the adhesive includes at least one of polyvinylidene fluoride, polyacrylate, polymethyl methacrylate, polyacrylonitrile, polyethylene oxide, and polyvinyl alcohol.

[0103] In one embodiment, the method for preparing the aluminum shell includes the following steps:

[0104] S1. After uniformly mixing ceramic particles and adhesive, thermal spraying technology is used to uniformly spray the coating onto the inner side of the aluminum shell and allow it to cool naturally to form an insulating layer.

[0105] S2. Mix the polymer matrix, additives and microencapsulated flame retardant evenly to obtain a mixture; then heat the mixture to the foaming temperature and add a foaming agent to foam it. After foaming, cool it and then bond the cooled product to the surface of the insulating layer of at least one of the first and second surfaces of the aluminum shell substrate to form a lithium plating optimization layer; thus obtaining the aluminum shell.

[0106] In one embodiment, the secondary battery further includes an electrolyte.

[0107] This application does not limit the composition of the electrolyte; any known electrolyte composition can be used to prepare the electrolyte.

[0108] In one embodiment, the core includes a positive electrode sheet, a negative electrode sheet, and a separator.

[0109] In one embodiment, the positive electrode includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector; the positive active material layer includes a positive active material. This application does not limit the positive active material; any known positive active material can be used.

[0110] In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material. This application does not limit the negative electrode active material; any known negative electrode active material can be used.

[0111] In one embodiment, the separator of the secondary battery is disposed between the positive and negative electrodes. This application does not limit the separator and known separators can be used, such as PE film, PP film or PP / PE composite film.

[0112] In one embodiment of this application, an electrical device is provided, which includes the secondary battery described in this application.

[0113] For example, the aforementioned electrical devices may include mobile devices (such as laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0114] Example 1

[0115] Embodiment 1 of this application provides a secondary battery, the preparation method of which includes the following steps:

[0116] (1) Preparation of microencapsulated flame retardants

[0117] Using polyethylene matrix as the capsule wall material and borate as the capsule core material, with a feeding ratio of 1:4 for the capsule wall and the capsule core, 3D printing was performed according to the parameters set for 3D printing to obtain microencapsulated flame retardant.

[0118] The obtained microencapsulated flame retardant has a mass ratio of capsule wall to capsule core of 1:4 and a diameter of 80 μm.

[0119] (2) Preparation of the core

[0120] S1. Preparation of positive electrode sheet: The positive electrode active material NCM613: conductive carbon black: polyvinylidene fluoride-trifluoroethylene = 96.5:2:1.5 by mass ratio is mixed, and the mixture is coated on aluminum foil after being mixed with denitromethylpyrrolidone as solvent and vacuum dried at 90℃ to obtain the positive electrode sheet.

[0121] S2. Preparation of negative electrode sheet: Graphite: conductive carbon black: sodium carboxymethyl cellulose: styrene-butadiene rubber in a mass ratio of 96.5:0.5:1.5:1.5, mixed with deionized water as solvent, coated onto copper foil, and dried under vacuum at 90°C to obtain negative electrode sheet.

[0122] S3. The PE diaphragm, positive electrode sheet and negative electrode sheet are wound to form a multi-tab battery cell, and then hot-pressed (pressure 0.4Mpa, time 8s, hot-pressing temperature 85℃) to obtain a wound core;

[0123] (3) Preparation of aluminum shell

[0124] S1. After uniformly mixing ceramic particles (AlN) and adhesive (polyvinylidene fluoride) at a mass ratio of 90:10, the mixture is sprayed evenly on the inside of the untreated aluminum shell using thermal spraying technology and allowed to cool naturally to form an insulating layer with a thickness of 0.12mm. Corresponding lithium plating optimization layer arc-shaped grooves are retained on the first and second surfaces (opposite surfaces of the core bending part) of the aluminum shell substrate.

[0125] S2. The polymer matrix (polyethylene), additives (mica powder), and microencapsulated flame retardant are mixed evenly at a mass ratio of 90:5:5 to obtain a mixture. Then, when the foaming mold is heated to the foaming temperature, the mixture is added into the mold and the mold is closed. Next, a foaming agent (carbon dioxide, with a mass ratio of foaming agent to polymer matrix of 90:10) is added to allow it to diffuse and decompose in the mold. After foaming, the mold is opened, pressure is released, and the product is cooled and demolded. The cooled and demolded product is then bonded to the surface of the insulation layer opposite to the curved part of the core, forming a layer with a thickness of 1.8 mm and a density of 0.3 g / cm³.3 The lithium plating optimization layer has an arc radius that is 0.8 mm larger than the radius of the bent part of the core. According to the test, the mass percentage of microencapsulated flame retardant in the lithium plating optimization layer is 5%.

[0126] The appearance diagram of the untreated aluminum shell is as follows: Figure 1 As shown; during the preparation process, the insulating layer is formed on surfaces 1, 2, 3, 4, and 5 of the aluminum shell, and the lithium plating optimization layer is formed on surfaces 1 and 2 of the aluminum shell; the top view of the processed aluminum shell is shown below. Figure 2 As shown;

[0127] (4) Preparation of secondary batteries

[0128] Two cores are grouped together and welded to the top cover. Then, laser welding is performed on the top cover, and an airtightness test is conducted to confirm that the aluminum shell is well welded. After that, the secondary battery is obtained through processes such as formation, high temperature aging, secondary liquid injection, sealing welding, and capacity testing.

[0129] The top view of the secondary battery is as follows: Figure 3 As shown.

[0130] In the following embodiments, the density of the lithium plating optimization layer is achieved by changing the amount of raw materials input; specifically, taking Example 1 as the standard, the types of raw materials remain unchanged, and the amount of raw materials input is changed accordingly based on the change in density to achieve the change in the density of the lithium plating optimization layer.

[0131] Example 2-3

[0132] This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the thickness, density, and capsule size of the lithium plating optimization layer are adjusted.

[0133] Examples 4-7

[0134] This application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the thickness of the lithium plating optimization layer is adjusted by changing the mold size used in the preparation of the lithium plating optimization layer.

[0135] Examples 8-11

[0136] This application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the density of the lithium plating optimization layer is changed by changing the amount of raw materials input (the mass ratio of microcapsules remains unchanged).

[0137] Examples 12-15

[0138] This application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the diameter of the microencapsulated flame retardant is changed by changing the parameters set during the 3D printing process.

[0139] Example 16

[0140] This application provides a secondary battery. The preparation method of the secondary battery differs from that of Example 1 in that the K value remains unchanged, and the capsule radius and lithium plating layer density are adjusted to optimize the process.

[0141] Example 17

[0142] This application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the diameter of the microencapsulated flame retardant is changed by adjusting the parameters of 3D printing, and the thickness of the lithium plating optimization layer is adjusted by adjusting the mold size used in the preparation of the lithium plating optimization layer.

[0143] Example 18

[0144] This application provides a secondary battery. The preparation method of the secondary battery differs from that of Example 1 in that the K value remains unchanged, while the thickness and density of the lithium plating optimization layer and the capsule size are adjusted.

[0145] Examples 19-22

[0146] This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the amount of microencapsulated flame retardant added during the preparation of the lithium plating optimization layer is changed.

[0147] Examples 23-26

[0148] This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the amount of raw materials added to the capsule wall and capsule core during the preparation of the microencapsulated flame retardant is changed.

[0149] Example 27

[0150] This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the polymer matrix is ​​a mixture of polyethylene and polypropylene in a 1:1 mass ratio.

[0151] Example 28

[0152] This application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the foaming agent (azodicarbonamide) and the foaming temperature are adjusted so that the pore structure of the lithium plating optimization layer is closed-cell.

[0153] Example 29

[0154] This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the lithium plating optimization layer is not arc-shaped, but rather... Figure 4 The mountain peak shape shown.

[0155] Example 30

[0156] This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the lithium plating optimization layer is not arc-shaped, but rather... Figure 5 The planar type shown.

[0157] Comparative Examples 1-2

[0158] This application provides a secondary battery in a comparative example. The difference between the preparation method of the secondary battery and that of Example 1 is that the thickness and density of the lithium plating optimization layer and the capsule size are changed so that the K value exceeds the specified range.

[0159] Comparative Example 3

[0160] This application provides a secondary battery in a comparative example. The difference between the preparation method of the secondary battery and that of Example 1 is that no microencapsulated flame retardant is added.

[0161] The parameters of the embodiments and comparative examples are shown in Table 1, and the parameter tests in Table 1 are as follows;

[0162] 1) The thickness of the lithium plating optimization layer was measured using an electronic digital micrometer, in mm, with an accuracy of 0.0.

[0163] 2) The density of the optimized lithium plating layer was obtained by analytical balance (mass) and water level method (volume) tests. Density = mass / volume, unit is g / cm³. 3 The accuracy is 0.00;

[0164] 3) The diameter of the microencapsulated flame retardant was measured by SEM or TEM, and the unit is μm;

[0165] 4) In the lithium plating optimization layer, the mass percentage of microencapsulated flame retardant was obtained through thermogravimetric analysis.

[0166] 5) The mass ratio of the microencapsulated flame retardant capsule wall to the capsule core was obtained through thermogravimetric analysis;

[0167] 6) The difference between the arc radius of the lithium plating optimization layer and the radius of the core bending section is obtained by calculation based on specifications or measurement with a ruler and distance sensor.

[0168] Table 1

[0169]

[0170]

[0171] Example of effect

[0172] The performance examples of this application test the performance of the prepared secondary battery, specifically including the following aspects:

[0173] 1) Fast charging cycle life test: The secondary battery was placed in an environment of 25℃ for 1 hour, charged at a constant current and constant voltage of 2.0C to 4.35V, and the cutoff current was 0.05C; it was discharged at a constant current of 0.5C, and the cutoff voltage was 2.8V. This is one complete charge and discharge cycle test. Repeat the charge and discharge cycle 3 times. The discharge capacity of the third cycle is used as the initial capacity. The number of cycles reached 1000 at room temperature. The capacity retention rate of the secondary battery was recorded, and the lithium plating and expansion state of the negative electrode corner area were observed by disassembly.

[0174] The lithium plating standards are as follows:

[0175] Severe lithium plating: Large areas of lithium plating (>1 / 4 of the corner area), grayish-white;

[0176] Medium-grade lithium plating: Small patches of lithium plating (>1 / 8 of the corner area), grayish-white;

[0177] Slight lithium plating: Piece-like lithium plating, light gray in color;

[0178] No lithium plating: No lithium plating, golden yellow color;

[0179] 2) The expansion state standard is as follows: The expansion force module is used to monitor the expansion force during the cycle of the secondary battery. The initial expansion force of the fixture is set to 300±10kgf, and the size of the secondary battery in the initial state is measured. As the cycle proceeds, the secondary battery expands, the expansion force module records the expansion force growth state, and the size of the secondary battery is measured after the cycle ends.

[0180] 3) Low-temperature lithium plating test: The secondary battery was placed in an environment of 25℃ for 1 hour, then charged at a constant current and constant voltage of 0.5C to 4.35V, with a cutoff current of 0.05C; it was then discharged at a constant current of 0.5C, with a cutoff voltage of 2.8V. This completes one charge-discharge cycle test. This charge-discharge cycle was repeated 3 times, with the discharge capacity of the third cycle as the initial capacity. The battery was then cycled 100 times at -10℃ with a constant current of 0.5C, during which the temperature of the secondary battery's corner area was monitored. The temperature was then adjusted to 25℃, placed in an environment of 3 hours, charged at a constant current and constant voltage of 0.5C to 4.35V, with a cutoff current of 0.05C, placed in an environment of 30 minutes, and disassembled to observe the lithium plating in the negative electrode corner area.

[0181] 4) Safety performance testing:

[0182] 1. Charge the secondary battery at a constant current and constant voltage rate of 0.5C to 4.35V, with a cutoff current of 0.05C;

[0183] 2. Using heating to trigger battery thermal runaway: In a fully enclosed enclosure, the heating element is placed tightly against the center of the wide surface of the secondary battery casing;

[0184] 3. Start the heating device to heat the secondary battery until the secondary battery experiences thermal runaway or exceeds the monitoring point temperature (300℃), then stop heating and record the time and phenomenon of the secondary battery igniting.

[0185] According to the national standard GB38031-2020, an alarm signal should be generated 5 minutes before thermal runaway of the battery causes thermal diffusion or even danger.

[0186] The results are shown in Table 2.

[0187] Table 2

[0188]

[0189]

[0190] As can be seen from Table 2, when the technical solution of this application is adopted, the obtained secondary battery has good room temperature and low temperature cycling stability and safety. Specifically, the capacity retention rate of the obtained battery after 1000 cycles is above 83.3%, and no moderate or severe lithium plating occurs in the corner area. The size of the corner area after cycling is less than 2.1 mm. After 100 cycles at low temperature, the temperature of the corner area is below 3.1℃, and no moderate or severe lithium plating occurs in the corner area. At the same time, the obtained secondary battery can meet the requirements of national standard GB38031-2020, which stipulates that the battery should not catch fire or the fire time should be more than 300 seconds.

[0191] As can also be seen from Examples 1 and Comparative Examples 1-3, excellent overall results can only be achieved when K is within the range given in this application and microencapsulated flame retardants are added.

[0192] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A secondary battery, comprising a winding core and an aluminum casing, the winding core having a flat portion and a curved portion, the aluminum casing comprising an aluminum casing base and an insulating layer disposed on the inner surface of the aluminum casing base, characterized in that, The aluminum shell substrate has a first side and a second side disposed opposite to each other; a lithium plating optimization layer is disposed on the insulating layer of at least one of the first side and the second side; the lithium plating optimization layer is disposed opposite to the core bending portion; The lithium plating optimization layer includes a microencapsulated flame retardant; The lithium plating optimization layer satisfies: 0.0006≤K≤0.07; Where K = a × b / d, a mm represents the thickness of the lithium plating optimization layer; the thickness a mm of the lithium plating optimization layer is 0.5-2.2 mm. bg / cm 3 The density of the lithium plating optimization layer; the density of the lithium plating optimization layer is bg / cm³. 3 It is 0.05-0.5 g / cm³. 3 ; d μm is the diameter of the microencapsulated flame retardant; the diameter d μm of the microencapsulated flame retardant is 10-200 μm.

2. The secondary battery according to claim 1, characterized in that, The lithium plating optimization layer comprises the following components by mass percentage: 90-97% polymer matrix, 2-8% microencapsulated flame retardant, and 1-8% additives.

3. The secondary battery according to claim 2, characterized in that, At least one of the following conditions must be met: d. The polymer matrix includes at least one of polyolefin, polyurethane, polystyrene, and polyvinyl chloride; e. The additives include at least one of mica powder, talc powder, glass powder, and calcium carbonate.

4. The secondary battery according to claim 1, characterized in that, The microencapsulated flame retardant comprises a capsule wall and a capsule core, wherein the mass ratio of the capsule wall to the capsule core is 1:(3-5).

5. The secondary battery according to claim 4, characterized in that, At least one of the following conditions must be met: f. The capsule wall comprises at least one of polyethylene, polypropylene, polystyrene, and polyamide; g. The core comprises at least one of alkyl phosphate flame retardants, aryl phosphate flame retardants, organic halogenated flame retardants, and inorganic flame retardants.

6. The secondary battery according to claim 1, characterized in that, The lithium plating optimization layer has an arc-shaped portion.

7. The secondary battery according to claim 6, characterized in that, The difference between the arc radius of the lithium plating optimization layer and the radius of the curved part of the core is 0.1-2.5 mm.

8. The secondary battery according to claim 1, characterized in that, The thickness of the insulating layer is 0.1-0.15 mm.

9. An electrical device, characterized in that, It includes the secondary battery as described in any one of claims 1-8.

Citation Information

Patent Citations

  • Secondary battery

    JP2010176901A

  • Electrode assembly, and electrochemical device and electronic device having same

    WO2021189454A1